2011
DOI: 10.1128/aem.02867-10
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Scale Visualization and Structural Analysis of the Inorganic/Organic Hybrid Structure of Gallionella ferruginea Twisted Stalks

Abstract: The so-called Fe/Mn-oxidizing bacteria have long been recognized for their potential to form extracellular iron hydroxide or manganese oxide structures in aquatic environments. Bacterial species belonging to the genus Gallionella, one type of such bacteria, oxidize iron and produce uniquely twisted extracellular stalks consisting of iron oxide-encrusted inorganic/organic fibers. This paper describes the ultrastructure of Gallionella cells and stalks and the visualized structural and spatial localization of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 24 publications
5
59
0
1
Order By: Relevance
“…1D, arrowhead). These features are consistent with earlier descriptions of Gallionella ferruginea (21,25,52). …”
Section: Resultssupporting
confidence: 82%
“…1D, arrowhead). These features are consistent with earlier descriptions of Gallionella ferruginea (21,25,52). …”
Section: Resultssupporting
confidence: 82%
“…2J), in which the intense red Fe signals are localized at the fiber margin, but the green and/or yellowish signals are not. Suzuki et al (15) detected similar Fe/C localization patterns in Gallionella stalk fibers using EELS and proposed that (i) the C fibrils probably excreted from the bacterial cells were intermingled and folded at the fiber core region but not at the extreme margin and (ii) oxidized Fe could interact with C in the entire fiber. The biotic and abiotic Fe (11) measured rates of biological and autocatalytic oxidation in Fe-oxidizing bacteriainhabiting mats and showed the same order of magnitude for both oxidations.…”
mentioning
confidence: 81%
“…Our previous EELS mapping (15) suggested that Fe could exist as iron oxide and/or oxyhydroxide in the fibers of G. ferruginea. It is likely that organic fibrils in the stalks and sheaths collect iron oxyhydroxides and control its recrystallization in the structures, which possibly explains the natural formation of the mineralized structures, as suggested by Chan et al (1, 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated Ni 2ϩ immobilization for stalks produced by microaerophilic Fe(II)-oxidizing bacteria collected from an abandoned mine. Sorption of other transition metals to twisted stalks has also been reported (31,34,35,37,63). Therefore, the presence of twisted stalks affects the availability of transition metals not only for the stalk-forming bacteria but also for other microorganisms.…”
Section: Figmentioning
confidence: 99%